Ascaroside Signaling in the Bacterivorous Nematode Encodes the Growth Phase of Its Bacterial Food Source. - Dolke, Franziska; Dong, Chuanfu; Bandi, Siva; Paetz, Christian; Glauser, Gaëtan; Von Reuss, Stephan (My University, 2019)
A novel class of species-specific modular ascarosides that integrate additional fatty acid building blocks was characterized in the nematode using a combination of HPLC-ESI-(-)-MS/MS precursor ion scanning, microreactions, HR-MS/MS, MS, and NMR techniques. The structure of the dominating component carrying a cyclopropyl fatty acid moiety was established by total synthesis. Biogenesis of this female-produced male attractant depends on cyclopropyl fatty acid synthase (), which is expressed in bacteria upon entering their stationary phase.